The Effect of Cooperative Learning Model Type Student Team Achievement Divisions (STAD) Assisted by Virtual Media on Students' Concept Mastery Ability - Abelia Berliana Casandra; Wahyudi; Aris Doyan; Sutrio (Postgraduate Program, University of Mataram, 2025)
This study aims to determine the effect of the Student Team Achievement Divisions (STAD) type cooperative learning model assisted by virtual media on students' concept mastery ability on static fluid material. The background of this study is based on the low level of mastery of students' concepts due to the dominance of conventional learning methods that lack interaction and the limited use of interactive learning media. This research is a quasi-experiment with a pretest-posttest control group design. The research subjects were students of class XI at SMAN 2 Mataram which were divided into experimental and control classes. The instrument used was a multiple choice test totaling 15 questions to measure concept mastery. The results showed that there was a significant increase in the posttest scores of students in the experimental class compared to the control class. The independent t-test showed a significance value <0.05, indicating a significant effect of the application of the STAD model assisted by virtual media on students' concept mastery. This finding shows that the combination of cooperative learning approach and virtual media such as PhET simulation and learning video is effective in increasing students' active participation, concept visualization, and understanding of physics materials.